Powder containing anionically modified cellulose nanofibers

By preparing anionically modified cellulose nanofiber powder with specific particle size and dispersion, the problem of the powder flying in the cellulose nanofiber drying body in the process is solved, and the effect of excellent processing and working properties is achieved.

CN119731245APending Publication Date: 2025-03-28NIPPON PAPER IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480003808.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-22
Filing Date
2024-02-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The dry body of cellulose nanofibers is prone to powder flying during the process, and the handling and working properties are poor.

Method used

By preparing powders with specific particle sizes and dispersion, the average fiber diameter is 3 nm to 500 nm, the moisture content is less than 20 mass%, the average particle size is more than 45 μm, the dispersion is less than 25%, and the angle of rest, collapse angle and difference angle are adjusted to optimize the handling and working properties of the powder.

Benefits of technology

The powder containing anion modified cellulose nanofibers with excellent processing and working properties is realized, reducing the powder scattering in the process, and improving the redispersion and initial water absorption of the powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A powder containing anion-modified cellulose nanofibers having an average fiber diameter of 3 nm to 500 nm, the powder having a water content of 20 mass% or less, an average particle diameter of 45 [mu] m or more, and a degree of dispersion of less than 25%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a powder containing anionically modified cellulose nanofibers. Background Art

[0002] It is known that when anionic groups such as carboxyl and carboxymethyl groups are introduced into cellulose molecular chains and mechanically treated (defibrated), they can be converted into cellulose nanofibers with nanometer-scale fiber diameters. Cellulose nanofibers are being studied for their application in various fields because they are light, strong, and biodegradable.

[0003] Usually, cellulose nanofibers introduced with anionic groups are manufactured in a state of being stably dispersed in water, and are usually used for various purposes as industrial materials or additives for food and cosmetics in the state of the manufactured cellulose nanofiber dispersion of a predetermined concentration. In order to stably maintain the state of the cellulose nanofibers, water of about several dozen times the amount of the cellulose nanofibers is required, but the high amount of water increases the cost of packaging, storage, and transportation of the cellulose nanofibers, so the cellulose nanofibers are dried to form a dry body, and water is added to redisperse the cellulose nanofibers when used, and the redispersed liquid is used.

[0004] When a water dispersion of cellulose nanofibers is dried to obtain a dry solid, hydrogen bonds are formed between fine cellulose fibers. Therefore, even if water is added to the dry solid to redisperse it, there is a problem that various properties such as viscosity will not be restored to the same level as before drying. Therefore, the drying method has been studied (Patent Document 1, etc.).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2019 / 189318 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The dried cellulose nanofibers are prepared by drying, crushing, classifying, and recovering the cellulose nanofibers dispersed in water (in a wet state). The cellulose nanofiber powder prepared in this way is redispersed by adding water to the product by the user and is used in various applications in the form of a redispersed liquid. However, due to the characteristics of the powder, the powder sometimes flies during the process, which makes the handling and workability poor.

[0010] Therefore, an object of the present invention is to provide a powder containing anionically modified cellulose nanofibers which is excellent in handling and workability.

[0011] Means for solving problems

[0012] The present inventors have conducted intensive studies to achieve the above object and have found that it is extremely effective to prepare a powder having a specific particle size and dispersion, thereby completing the present invention.

[0013] The present invention provides the following contents.

[0014] (1) A powder containing anionic modified cellulose nanofibers, comprising anionic modified cellulose nanofibers with an average fiber diameter of 3 nm to 500 nm, wherein the powder containing anionic modified cellulose nanofibers has a moisture content of 20% by mass or less, an average particle size of 45 μm or more, and a dispersion degree of less than 25%.

[0015] (2) The powder containing anionically modified cellulose nanofibers according to (1), wherein the angle of repose of the powder containing anionically modified cellulose nanofibers is 40° to 49°.

[0016] (3) The powder containing anionically modified cellulose nanofibers according to (1), wherein the powder containing anionically modified cellulose nanofibers has a collapse angle of 15° to 24°.

[0017] (4) The powder containing anionically modified cellulose nanofibers according to (1), wherein the difference angle of the powder containing anionically modified cellulose nanofibers is 20° to 25°.

[0018] Effects of the Invention

[0019] According to the present invention, a powder containing anionically modified cellulose nanofibers which is excellent in handling and workability can be provided. DETAILED DESCRIPTION

[0020] The present invention is described in detail below. In the present invention, "~" includes both end values. That is, "X~Y" includes both end values ​​X and Y.

[0021] (Powder containing anionic modified cellulose nanofibers)

[0022] The present invention is a powder containing anionically modified cellulose nanofibers (anionically modified CNF) having an average fiber diameter of 3 nm to 500 nm, a moisture content of 20 mass % or less, an average particle size of 45 μm or more, and a dispersion degree of less than 25%.

[0023] (Water content)

[0024] From the perspective of storage stability, the moisture content of the powder containing anion-modified CNF of the present invention is 20% by mass or less, preferably 0% to 15% by mass, more preferably 0% to 10% by mass, and further preferably 0% to 9.5% by mass. When the moisture content is too much relative to the above upper limit, there is a problem of increased possibility of corruption. It can also be dried to a moisture content of 0% (absolute dryness).

[0025] (Average particle size)

[0026] From the viewpoint of easy handling, the lower limit of the average particle size of the powder containing anion-modified CNF of the present invention is 45 μm or more, preferably 50 μm or more, more preferably 60 μm or more, and the upper limit is 300 μm or less, preferably 250 μm or less, more preferably 150 μm or less. When the average particle size is too small relative to the above value, there is a problem of easy scattering and difficult to handle. Here, the average particle size (D50) is the particle size that is accumulated from the minimum value in the volume-based particle size distribution and contains 50%. The particle size distribution can be measured using a laser diffraction scattering particle size distribution instrument.

[0027] (Dispersion)

[0028] From the viewpoint of handling and operability, the dispersion of the powder containing anion-modified CNF of the present invention is less than 25%, preferably less than 20%. The lower limit is preferably 8% or more. When the dispersion is within the above range, the amount of scattering in the process is small, and the handling and operability are excellent. When the dispersion is too large, the amount of scattering in the process increases, and the handling is poor. In addition, poor sealing during packaging occurs, and the operability is poor. On the other hand, when the dispersion is too small, the jetting is low and the fluidity is low, so it is easy to be blocked. The dispersion can be measured using a powder tester.

[0029] (angle of repose)

[0030] From the viewpoint of handling and workability, the angle of repose of the powder containing anion-modified CNF of the present invention is preferably 40° to 49°, more preferably 42° to 48°. When the angle of repose is too large relative to the above range, accumulation is likely to occur in the hopper, and when the angle of repose is too small relative to the above range, the powder cannot stop from the discharge port of the feeder, etc. The angle of repose can be measured using a powder property tester.

[0031] (Crash Angle)

[0032] From the viewpoint of handling and workability, the collapse angle of the powder containing anion-modified CNF of the present invention is preferably 15° to 24°, more preferably 17° to 22°. When the collapse angle is too large relative to the above range, a large impact is required to collapse the volume of the powder. When the collapse angle is too small relative to the above range, the powder cannot stop from the discharge port of the feeder, etc. The collapse angle can be measured using a powder property tester.

[0033] (Difference angle)

[0034] From the viewpoint of handling and workability, the difference angle of the powder containing anion-modified CNF of the present invention is preferably 20° to 25°, more preferably 21° to 25°. When the difference angle is too large relative to the above range, the jet property becomes high and the powder is easy to scatter. When the difference angle is too small relative to the above range, the discharge requires a large force and it is difficult to control the discharge amount. The difference angle can be obtained by the following formula from the angle of repose and the angle of collapse measured using a powder property tester.

[0035] Differential angle = repose angle - collapse angle

[0036] (Anion-modified cellulose nanofibers)

[0037] In the present invention, anionically modified cellulose nanofibers (anionically modified CNFs) are fine fibers having an average fiber diameter (fiber width) of 3 nm to 500 nm and an aspect ratio of 100 or more, and can be obtained by defibrillating anionically modified cellulose.

[0038] (Cellulose raw materials)

[0039] Examples of the cellulose raw material for producing the anion-modified cellulose include cellulose raw materials derived from plant materials (e.g., wood, bamboo, hemp, jute, kenaf, agricultural waste residues, cloth, pulp (coniferous unbleached kraft pulp (NUKP), coniferous bleached kraft pulp (NBKP), broadleaf unbleached kraft pulp (LUKP), broadleaf bleached kraft pulp (LBKP), coniferous unbleached sulfite pulp (NUSP), coniferous bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), recycled pulp, waste paper, etc.), animal materials (e.g., ascidian species), algae, microorganisms (e.g., acetic acid bacteria (Acetobacter genus)), microbial products, and the like, and any of them can be used. Cellulose fibers derived from plants or microorganisms are preferred, and cellulose fibers derived from plants are more preferred.

[0040] (Anion modification)

[0041] In the present invention, anionic modification refers to the introduction of anionic groups into cellulose, specifically, the introduction of anionic groups on the pyranose ring of cellulose by carboxylation (oxidation) or substitution reaction. In the present invention, the carboxylation (oxidation) reaction refers to the direct oxidation of the hydroxyl group of the pyranose ring to a carboxyl group. In addition, in the present invention, the substitution reaction refers to the introduction of anionic groups on the pyranose ring by substitution reactions other than the carboxylation (oxidation).

[0042] Examples of anion modification include carboxylation (oxidation), carboxymethylation, esterification, etc. Among them, carboxylation (oxidation), carboxymethylation, and phosphate esterification are more preferred, and carboxylation (oxidation) is particularly preferred.

[0043] (Carboxylation)

[0044] In the present invention, when carboxylated (oxidized) cellulose is used as the anion-modified cellulose, the carboxylated cellulose (also referred to as oxidized cellulose) can be obtained by carboxylating (oxidizing) the above-mentioned cellulose raw material by a known method. Although not particularly limited, during carboxylation, the amount of carboxyl groups is preferably adjusted to 0.6 mmol / g to 2.0 mmol / g, and more preferably to 1.0 mmol / g to 2.0 mmol / g, relative to the absolute dry mass of the anion-modified cellulose nanofibers.

[0045] As an example of the carboxylation (oxidation) method, there can be cited a method in which a cellulose raw material is oxidized in water using an oxidant in the presence of an N-oxyl compound and a compound selected from the group consisting of bromide, iodide or a mixture thereof. By this oxidation reaction, the primary hydroxyl group at the C6 position of the pyranose glucopyranose ring on the surface of the cellulose is selectively oxidized to obtain a cellulose having an aldehyde group and a carboxyl group (-COOH) or an aldehyde group and a carboxylate group (-COO - The concentration of cellulose during the reaction is not particularly limited, but is preferably 5% by mass or less.

[0046] The N-oxyl compound refers to a compound that can generate a nitroxyl radical. As the N-oxyl compound, any compound can be used as long as it promotes the target oxidation reaction. Examples thereof include 2,2,6,6-tetramethylpiperidin-1-oxyl radical (TEMPO) and its derivatives (e.g., 4-hydroxy TEMPO).

[0047] The amount of the N-oxyl compound used is not particularly limited as long as it is a catalytic amount capable of oxidizing the cellulose as a raw material. For example, it is preferably 0.01 mmol to 10 mmol, more preferably 0.01 mmol to 1 mmol, and further preferably 0.05 mmol to 0.5 mmol relative to 1 g of absolutely dry cellulose. In addition, it can be about 0.1 mmol / L to about 4 mmol / L relative to the reaction system.

[0048] Bromide refers to a compound containing bromine, and examples thereof include alkali metal bromides that can dissociate and ionize in water. In addition, iodide refers to a compound containing iodine, and examples thereof include alkali metal iodides. The amount of bromide or iodide used can be selected from a range that can promote the oxidation reaction. The total amount of bromide and iodide is, for example, preferably 0.1 mmol to 100 mmol, more preferably 0.1 mmol to 10 mmol, and further preferably 0.5 mmol to 5 mmol relative to 1 g of absolute dry cellulose.

[0049] As the oxidant, a known oxidant can be used, for example, halogen, hypohalous acid, halogenous acid, perhalogen acid or their salts, halogen oxides, peroxides, etc. can be used. Among them, sodium hypochlorite, which is cheap and has a small environmental load, is preferred. The appropriate amount of the oxidant used is, for example, preferably 0.5 mmol to 500 mmol, more preferably 0.5 mmol to 50 mmol, further preferably 1 mmol to 25 mmol, and most preferably 3 mmol to 10 mmol, relative to 1 mol of the N-oxyl compound. In addition, for example, it is preferably 1 mol to 40 mol relative to 1 mol of the N-oxyl compound.

[0050] The cellulose oxidation process can react efficiently even under relatively mild conditions. Therefore, the reaction temperature is preferably 4°C to 40°C, and can also be room temperature of about 15°C to about 30°C. As the reaction proceeds, carboxyl groups are generated in cellulose, so it is confirmed that the pH of the reaction solution decreases. In order to make the oxidation reaction proceed efficiently, it is preferred to add an alkaline solution such as an aqueous sodium hydroxide solution to maintain the pH of the reaction solution at 8 to 12, preferably about 10 to about 11. In terms of ease of handling and difficulty in causing side reactions, the reaction medium is preferably water.

[0051] The reaction time in the oxidation reaction can be appropriately set depending on the degree of progress of the oxidation, and is generally 0.5 to 6 hours, for example, about 0.5 to 4 hours.

[0052] In addition, the oxidation reaction can be carried out in two stages. For example, by oxidizing the cellulose obtained by filtration after the first stage reaction under the same or different reaction conditions, the oxidation can be carried out efficiently while avoiding the reaction inhibition caused by the salt produced as a by-product in the first stage reaction.

[0053] As another example of the carboxylation (oxidation) method, there can be cited a method of oxidizing by contacting a gas containing ozone with a cellulose raw material. By this oxidation reaction, at least the hydroxyl groups at positions 2 and 6 of the pyranose glucopyranose ring are oxidized, and the cellulose chain is decomposed. The ozone concentration in the ozone-containing gas is preferably 50 g / m 3 ~250g / m 3 , more preferably 50g / m 3 ~220g / m 3 . When the solid content of the cellulose raw material is set to 100 parts by mass, the amount of ozone added to the cellulose raw material is preferably 0.1 parts by mass to 30 parts by mass, and more preferably 5 parts by mass to 30 parts by mass. The ozone treatment temperature is preferably 0°C to 50°C, and more preferably 20°C to 50°C. The ozone treatment time is not particularly limited, and is about 1 minute to about 360 minutes, and preferably about 30 minutes to about 360 minutes. When the conditions of the ozone treatment are within these ranges, excessive oxidation and decomposition of cellulose can be prevented, and the yield of oxidized cellulose becomes good. After the ozone treatment is implemented, an additional oxidation treatment can be performed using an oxidant. The oxidant used for the additional oxidation treatment is not particularly limited, and chlorine compounds such as chlorine dioxide and sodium chlorite, oxygen, hydrogen peroxide, persulfuric acid, peracetic acid, etc. can be listed. For example, an oxidant solution can be prepared by dissolving these oxidants in a polar organic solvent such as water or alcohol, and the cellulose raw material can be immersed in the solution for additional oxidation treatment.

[0054] The amount of carboxyl groups in the oxidized cellulose can be adjusted by controlling the reaction conditions such as the amount of the oxidizing agent added and the reaction time.

[0055] (Carboxymethylation)

[0056] In the present invention, when carboxymethylated cellulose is used as an anion-modified cellulose, the carboxymethylated cellulose can be obtained by carboxymethylating the above-mentioned cellulose raw material by a known method, or a commercial product can be used. In either case, the degree of carboxymethyl substitution of each anhydroglucose unit of the cellulose is preferably 0.01 to 0.50. As an example of a method for manufacturing such carboxymethylated cellulose, the following method can be cited. Cellulose is used as a starting material, and as a solvent, 3 to 20 times the mass of water and / or lower alcohols, specifically water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, etc., are used as a single medium or a mixed medium of more than two. It should be noted that the mixing ratio of the lower alcohol when mixing the lower alcohol is 60% to 95% by mass. As a mercerizing agent, an alkali metal hydroxide of 0.5 to 20 times the mole of each anhydroglucose residue relative to the starting material is used, specifically sodium hydroxide and potassium hydroxide. The starting material is mixed with a solvent and a mercerizing agent, and mercerization treatment is performed under the conditions of a reaction temperature of 0°C to 70°C, preferably 10°C to 60°C, and a reaction time of 15 minutes to 8 hours, preferably 30 minutes to 7 hours. Then, a carboxymethylating agent is added in an amount of 0.05 to 10.0 times the mole per glucose residue, and an etherification reaction is performed under the conditions of a reaction temperature of 30°C to 90°C, preferably 40°C to 80°C, and a reaction time of 30 minutes to 10 hours, preferably 1 hour to 4 hours.

[0057] (Crystallinity of Cellulose Type I)

[0058] The crystallinity of cellulose type I in carboxymethylated cellulose is preferably 50% or more, more preferably 60% or more. The crystallinity of cellulose type I in carboxymethylated cellulose can be controlled by the concentration of the mercerizing agent during manufacture, the temperature during treatment, and the degree of carboxymethylation. In mercerization and carboxymethylation, since a high concentration of alkali is used, type I crystals of cellulose are easily converted into type II. For example, the degree of conversion can be adjusted by adjusting the amount of alkali (mercerizing agent) used to maintain the desired crystallinity. The upper limit of the crystallinity of cellulose type I is not particularly limited. In fact, it is believed that about 90% is the upper limit. The crystallinity of cellulose type I of carboxymethylated cellulose is generally the same as the crystallinity of cellulose type I of carboxymethylated CNF obtained by defibrating it.

[0059] It should be noted that in this specification, "carboxymethylated cellulose" as a kind of anion-modified cellulose used in the preparation of anion-modified CNF refers to cellulose in which at least a part of the fibrous shape is maintained even when dispersed in water. Therefore, it is distinguished from the carboxymethyl cellulose as a water-soluble polymer described later. When the aqueous dispersion of "carboxymethylated cellulose" is observed with an electron microscope, a fibrous substance can be observed. On the other hand, even when the aqueous dispersion of carboxymethyl cellulose as a water-soluble polymer is observed, no fibrous substance is observed. In addition, for "carboxymethylated cellulose", when measured by X-ray diffraction, the peak of cellulose type I crystals can be observed, but cellulose type I crystals are not observed in the carboxymethyl cellulose as a water-soluble polymer.

[0060] (Esterification)

[0061] In the present invention, when esterified cellulose is used as the anion-modified cellulose, the esterified cellulose can be obtained by a method of mixing a powder and an aqueous solution of a phosphate compound A with the above-mentioned cellulose raw material, or by a method of adding an aqueous solution of the phosphate compound A to a slurry of the cellulose raw material.

[0062] As the phosphoric acid compound A, phosphoric acid, polyphosphoric acid, phosphorous acid, hypophosphorous acid, phosphonic acid, polyphosphonic acid or their esters can be listed. They can also be in the form of salts. Among these, from the perspective of low cost, easy handling, and the introduction of phosphoric acid groups into the cellulose of pulp fibers to achieve the improvement of the defibrination efficiency, compounds with phosphoric acid groups are preferred. As compounds with phosphoric acid groups, phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium phosphite, potassium phosphite, sodium hypophosphite, potassium hypophosphite, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, ammonium metaphosphate, etc. They can be used in one or in combination of two or more. Among these, from the perspective of high efficiency of introducing phosphoric acid groups, easy defibrination in the following defibrination process, and easy to apply industrially, phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid are more preferred. Sodium dihydrogen phosphate and disodium hydrogen phosphate are particularly preferred. In addition, from the perspective of improving the uniformity of the reaction and improving the efficiency of introducing phosphate groups, the phosphate compound A is preferably used in the form of an aqueous solution. From the perspective of improving the efficiency of introducing phosphate groups, the pH of the aqueous solution of the phosphate compound A is preferably 7 or less, and from the perspective of inhibiting the hydrolysis of pulp fibers, it is preferably pH 3 to 7.

[0063] As an example of a method for producing phosphated cellulose, the following method can be cited. In a dispersion of a cellulose raw material having a solid content concentration of 0.1% to 10% by mass, a phosphoric acid compound A is added while stirring to introduce a phosphoric acid group into the cellulose. When the cellulose raw material is set to 100 parts by mass, the amount of the phosphoric acid compound A added is preferably 0.2 parts by mass to 500 parts by mass, and more preferably 1 part by mass to 400 parts by mass, based on the amount of phosphorus element. If the proportion of the phosphoric acid compound A is above the lower limit, the yield of the fine cellulose fibers can be further improved. However, when the upper limit is exceeded, the effect of improving the yield reaches saturation, so it is not preferred from a cost perspective.

[0064] At this time, in addition to the cellulose raw material and the phosphoric acid compound A, a powder or aqueous solution of a compound B other than these may be mixed. Compound B is not particularly limited, and is preferably a nitrogen-containing compound showing alkalinity. Here, "alkalinity" is defined as a pink to red aqueous solution or a pH of the aqueous solution greater than 7 in the presence of a phenolphthalein indicator. The nitrogen-containing compound showing alkalinity used in the present invention is not particularly limited as long as it exerts the effect of the present invention, and is preferably a compound having an amino group. For example, urea, methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, hexamethylenediamine, etc. can be cited without particular limitation. Among them, urea, which is low-cost and easy to handle, is preferred. The amount of compound B added is preferably 2 to 1000 parts by mass, and more preferably 100 to 700 parts by mass, relative to 100 parts by mass of the solid content of the cellulose raw material. The reaction temperature is preferably 0°C to 95°C, and more preferably 30°C to 90°C. The reaction time is not particularly limited, and is about 1 minute to about 600 minutes, and more preferably 30 minutes to 480 minutes. When the conditions of the esterification reaction are within these ranges, the cellulose can be prevented from being over-esterified and becoming easily soluble, and the yield of the phosphated cellulose becomes good. After the obtained phosphated cellulose suspension is dehydrated, it is preferably heated at 100°C to 170°C from the viewpoint of inhibiting the hydrolysis of cellulose. In addition, it is preferred that the heating is performed at 130°C or less, preferably 110°C or less during the heat treatment while water is contained, and the heat treatment is performed at 100°C to 170°C after the water is removed.

[0065] The degree of substitution of phosphate groups per glucose unit of the cellulose after phosphate esterification is preferably 0.001 to 0.40. By introducing phosphate group substituents into cellulose, celluloses are electrically repelled from each other. Therefore, cellulose into which phosphate groups have been introduced can be easily defibrated. It should be noted that when the degree of substitution of phosphate groups per glucose unit is less than 0.001, defibration cannot be fully performed. On the other hand, when the degree of substitution of phosphate groups per glucose unit is greater than 0.40, swelling or dissolution occurs, so that sometimes fine cellulose fiber form cannot be obtained. In order to perform defibration efficiently, it is preferred to boil the cellulose raw material after phosphate esterification obtained above and then wash it with cold water to perform washing. These modifications caused by esterification are modifications caused by substitution reactions. The degree of substitution in esterified cellulose is generally the same as the degree of substitution when the esterified cellulose is micronized.

[0066] Cellulose after phosphate esterification can also be referred to as cellulose into which a phosphorus oxyacid group or a substituent derived from a phosphorus oxyacid group as an anionic group is introduced (sometimes also referred to as a "phosphorus oxyacid group"). Here, as a phosphorus oxyacid group, for example, a divalent functional group equivalent to a group after removing a hydroxyl group from phosphoric acid, specifically a group represented by -PO3H2. Substituents derived from phosphorus oxyacid groups include substituents such as salts of phosphorus oxyacid groups and phosphorus oxyacid ester groups. It should be noted that substituents derived from phosphorus oxyacid groups can also be included in cellulose nanofibers as groups (such as pyrophosphate groups) obtained by condensation of phosphoric acid groups. In addition, the phosphorus oxyacid group can be, for example, a phosphorous acid group (phosphonic acid group), and the substituents derived from the phosphorus oxyacid group can be salts of phosphorous acid groups, etc.

[0067] There is no particular limitation on the amount of phosphorus oxyacid groups such as phosphate groups or phosphite groups introduced into the phosphated cellulose. During phosphate esterification, the amount of phosphorus oxyacid groups is preferably adjusted to 0.5 mmol / g to 5 mmol / g, more preferably 0.5 mmol / g to 2.5 mmol / g, relative to the absolute dry mass of the anion-modified cellulose nanofibers.

[0068] (Fiber removal)

[0069] There is no particular limitation on the device used when the anionic modified cellulose is defibrated, and devices such as high-speed rotary, colloid mill, high pressure, roller mill, and ultrasonic can be used. When defibration, it is preferred to apply a strong shear force to the aqueous dispersion of the anionic modified cellulose. In particular, in order to efficiently defibrate, it is preferred to use a wet high pressure or ultra-high pressure homogenizer that can apply a pressure of more than 50MPa and a strong shear force to the aqueous dispersion. The pressure is more preferably more than 100MPa, and more preferably more than 140MPa. In addition, it is also possible to pre-treat the aqueous dispersion using a known mixing, stirring, emulsifying, and dispersing device such as a high-speed shear mixer as needed before the defibration and dispersion treatment in the high-pressure homogenizer.

[0070] (Dispersant)

[0071] From the viewpoint of improving redispersibility, the powder containing anionically modified cellulose nanofibers of the present invention preferably contains a dispersant. As the dispersant, water-soluble polymers, surfactants, etc. can be cited. When a water-soluble polymer is used, the portion with low charge density on the surface of the anionically modified cellulose nanofibers is covered, and the formation of hydrogen bonds is suppressed to prevent the cellulose nanofibers from agglomerating with each other during drying. Therefore, a water-soluble polymer is preferably used.

[0072] (Water-soluble polymer)

[0073] In the present invention, examples of water-soluble polymers include cellulose derivatives (carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, ethyl cellulose), xanthan gum, xyloglucan, dextrin, dextran, carrageenan, locust bean gum, alginic acid, alginate, pullulan, starch, potato starch, arrowroot starch, processed starch (cationized starch, phosphorylated starch, phosphoric acid cross-linked starch, phosphoric acid monoesterified phosphoric acid cross-linked starch, hydroxypropyl starch, hydroxypropyl phosphoric acid cross-linked starch, acetylated adipic acid cross-linked starch, acetylated phosphoric acid cross-linked starch, acetylated oxidized starch, sodium starch octenylsuccinate, acetic starch, oxidized starch), corn starch, gum arabic, Gellan gum, polydextrose, pectin, chitin, water-soluble chitin, chitosan, casein, albumin, soy protein dissolution, peptone, polyvinyl alcohol, polyacrylamide, sodium polyacrylate, polyvinyl pyrrolidone, polyvinyl acetate, polyamino acid, polylactic acid, polymalic acid, polyglycerol, latex, rosin sizing agent, petroleum resin sizing agent, urea resin, melamine resin, epoxy resin, polyamide resin, polyamide-polyamine resin, polyethyleneimine, polyamine, vegetable glue, polyethylene oxide, hydrophilic cross-linked polymer, polyacrylic acid salt, starch polyacrylic acid copolymer, tamarind gum, guar gum and colloidal silicon dioxide and a mixture of more than one thereof. Wherein, from the aspect of compatibility with anion modified cellulose nanofiber, preferably cellulose derivatives, particularly preferably carboxymethyl cellulose and its salt. It is believed that water-soluble polymers such as carboxymethyl cellulose and its salt improve redispersibility by entering between anion modified cellulose nanofibers and expanding the distance between CNF.

[0074] As a water-soluble polymer, when carboxymethyl cellulose or its salt is used, it is preferred to use a carboxymethyl cellulose having a carboxymethyl substitution degree of 0.55 to 1.6 per anhydroglucose unit, more preferably a carboxymethyl cellulose of 0.55 to 1.1, and further preferably a carboxymethyl cellulose of 0.65 to 1.1. In addition, carboxymethyl cellulose with a long molecule (high viscosity) has a high effect of expanding the distance between CNFs, so it is preferred that the B-type viscosity of a 1% by mass aqueous solution of carboxymethyl cellulose at 25°C and 600rpm is preferably 3mPa·s to 14000mPa·s, more preferably 7mPa·s to 14000mPa·s, and further preferably 1000mPa·s to 8000mPa·s. It should be noted that the "carboxymethyl cellulose or its salt" as a water-soluble polymer mentioned here refers to a substance that is completely soluble in water, and is therefore distinguished from the above-mentioned carboxymethylated cellulose whose fiber shape can be confirmed in water.

[0075] In the present invention, when a dispersant is contained in the powder containing anion-modified cellulose nanofibers, the mixing ratio of anion-modified CNF (absolute dry solid content) to dispersant is preferably 2:8 to 8:2, and more preferably 5:5 to 7:3, from the viewpoint of obtaining an effect of improving redispersibility. When the mixing ratio of the dispersant is too much relative to the upper limit, problems such as reduced viscosity characteristics such as thixotropy and dispersion stability, which are characteristics of anion-modified CNF, may occur. When the mixing ratio of the dispersant is too little relative to the lower limit, sufficient redispersibility cannot be obtained.

[0076] (Method for producing powder)

[0077] The method for producing the powder containing anion-modified CNF of the present invention is not particularly limited. For example, the following methods can be cited: a method of dehydrating and drying an aqueous suspension containing anion-modified CNF and a dispersant as required to obtain a dry solid, then pulverizing the solid using a pulverizer, etc., and classifying and recovering the pulverized solid as required to obtain a powder; and a method of spray-drying the aqueous suspension to simultaneously dehydrate, dry and pulverize the solid, and classifying and recovering the solid as required to obtain a powder.

[0078] As a method for dehydrating and drying an aqueous suspension containing anion-modified CNF, it can be a known method in the past, for example, spray drying, freeze drying, squeezing, air drying, hot air drying and vacuum drying. As an example of a drying device specifically used, the following drying device can be cited. That is, a continuous tunnel drying device, a belt drying device, a vertical drying device, a vertical turbine drying device, a multi-stage circular plate drying device, a ventilation drying device, a rotary drying device, an airflow drying device, a spray dryer drying device, a spray dryer, a drum drying device, a reduced pressure belt drying device, a screw conveyor drying device, a rotary drying device with a heating tube, a vibration conveying drying device, a fluidized bed drying device, etc., a batch box drying device, a ventilation drying device, a vacuum box drying device, a stirring drying device, a shelf drying device, a freeze drying device and other drying devices can be used alone or in combination of two or more. Wherein, preferably a drum drying device and a belt drying device are used, and from the viewpoint of energy efficiency, it is further preferably used to evenly and directly supply heat energy to the dried object.

[0079] The method of obtaining a pulverized product by pulverizing a dry solid containing anion-modified CNF is not particularly limited. For example, a pulverized product can be obtained by pulverizing a dry solid containing anion-modified CNF using a pulverizer. As a pulverizer, for example, a cutting mill can be exemplified: a mesh mill (manufactured by Horai Co., Ltd.), Atoms (manufactured by Yamamoto Hyakuma Co., Ltd.), a knife mill (manufactured by Pallmann Co., Ltd.), a cutting mill (manufactured by Tokyo Atomizer Manufacturing Co., Ltd.), a CS cutter (manufactured by Mitsui Mining Co., Ltd.), a rotary cutting mill (manufactured by Nara Machinery Co., Ltd.), a turbo cutter (manufactured by Freund Sangyo Co., Ltd.), a pulp coarse crusher (manufactured by Zuiko Co., Ltd.), a shredder (manufactured by Kobelco Pantech Co., Ltd.), etc.; a hammer mill: a jaw crusher (manufactured by Makino Co., Ltd.), a hammercrusher (manufactured by Makino Sangyo Co., Ltd.);Impact mill: Pulverizer (manufactured by Hosokawa Micron Co., Ltd.), Fine impact mill (manufactured by Hosokawa Micron Co., Ltd.), Super Micron Mill (manufactured by Hosokawa Micron Co., Ltd.), Innomizer (manufactured by Hosokawa Micron Co., Ltd.), Fine Mill (manufactured by Nippon Pneumatic Industries, Ltd.), CUM type centrifugal mill (manufactured by Mitsui Mining Co., Ltd.), Exceed Mill (manufactured by Makino Sangyo Co., Ltd.), Ultraplex (manufactured by Makino Sangyo Co., Ltd.), Contraplex (manufactured by Makino Sangyo Co., Ltd.), Kolloplex (manufactured by Makino Sangyo Co., Ltd.), Sample mill (manufactured by Seishin Co., Ltd.), Bantam mill (manufactured by Seishin Co., Ltd.), Atomizer (manufactured by Seishin Co., Ltd.), Tornado Mill (manufactured by Nikkiso Co., Ltd.), Nair Mill (manufactured by Dalton Co., Ltd.), HT type fine pulverizer (manufactured by Horai Co., Ltd.), free pulverizer (manufactured by Nara Machinery Co., Ltd.), New Cosmomizer (manufactured by Nara Machinery Co., Ltd.), Turbo mill (manufactured by Freund Industry Co., Ltd.), Gather mill (manufactured by Nishimura Machinery Co., Ltd.), Super powder mill (manufactured by Nishimura Machinery Co., Ltd.), Blade mill (manufactured by Nissin Engineering Co., Ltd.), Super rotor (manufactured by Nissin Engineering Co., Ltd.), Npacrusher (manufactured by Misho Industry Co., Ltd.), Wheeley pulverizer (manufactured by Miki Co., Ltd.), pulp pulverizer (manufactured by Zuiko Co., Ltd.), Jakobson fine pulverizer (manufactured by Kobelco Pantech Co., Ltd.), Universalmill (manufactured by Tokuju Works Co., Ltd.), Atomizer (manufactured by Tokyo Atomizer Co., Ltd.), MillStardom (manufactured by Tokyo Atomizer Co., Ltd.);Air flow mill: Stream mill (manufactured by Nippon Coke Industry Co., Ltd.), CGS type Jet mill (manufactured by Mitsui Mining Co., Ltd.), Micron Jet (manufactured by Hosokawa Micron Co., Ltd.), Counter jet mill (manufactured by Hosokawa Micron Co., Ltd.), Cross jet mill (manufactured by Kurimoto Iron Works Co., Ltd.), Supersonic Jet mill (manufactured by Nippon Pneumatic Industry Co., Ltd.), Current Jet (manufactured by Nissin Engineering Co., Ltd.), Jet mill (manufactured by Misho Industry Co., Ltd.), Ebara Jet Micronizer (manufactured by Ebara Co., Ltd.), Ebara Triad Jet (manufactured by Ebara Co., Ltd.), Ceren Miller (manufactured by Masuyuki Sangyo Co., Ltd.), New Micro Sictomat (manufactured by Masuno Seisakusho Co., Ltd.), Kryptron (manufactured by Kawasaki Heavy Industries, Ltd.); disc mills: vibrating disc mill (manufactured by Retsch), Centricutter (manufactured by Nippon Coke Industry Co., Ltd.), Turbo disc mill (manufactured by Freund-Turbo Co., Ltd.), mortar-type high-speed pulverizer (manufactured by Makino Sangyo Co., Ltd.); vertical roller mills: vertical roller mill (manufactured by Scenion Co., Ltd.), vertical roller mill (manufactured by Schaeffler Japan Co., Ltd.), roller mill (manufactured by Kotobuki Giken Kogyo Co., Ltd.), VX mill (manufactured by Kurimoto Iron Works Co., Ltd.), KVM vertical mill (manufactured by Earth Technica Co., Ltd.), IS mill (manufactured by IHI Plant Engineering Co., Ltd.), etc.;

[0080] The processing conditions of these pulverizers cannot be uniformly specified due to the different pulverization principles. For example, the following method can be used: adjust the sieve diameter at the pulverizer outlet, the rotation speed of the grading rotor and other processing conditions that affect the pulverization process, prepare a calibration curve showing the relationship between the processing conditions and the particle size, and determine the appropriate processing conditions based on the calibration curve to achieve the desired average particle size.

[0081] The pulverized material containing anion-modified CNF may be classified as necessary, and in the case of classification, it may be performed using a classifying device attached to or mounted on a pulverizer.

[0082] The type of apparatus for recovering the pulverized product containing anion-modified CNF and the granulated product obtained by spray drying is not particularly limited. Examples of the recovery apparatus include a cyclone separator and a bag filter.

[0083] The powder containing anion-modified CNF may be a powder obtained by classification after recovery.

[0084] The anion-modified CNF-containing powder of the present invention has an average particle size of 45 μm or more and a dispersion degree of less than 25%, so that there is little powder flying in the process, the handling is excellent, and the workability during the redispersion operation is excellent. In addition, the anion-modified CNF-containing powder of the present invention has excellent initial water absorption.

[0085] Example

[0086] Hereinafter, the present invention will be described in further detail with reference to Examples, but the present invention is not limited thereto.

[0087] (Average fiber diameter and average fiber length of CNF)

[0088] The powder was redispersed in water to obtain a suspension, which was diluted, and 200 randomly selected fibers were analyzed using an atomic force microscope (AFM) to obtain an average value.

[0089] It should be noted that the aspect ratio is calculated by the following formula.

[0090] Aspect ratio = average fiber length / average fiber diameter

[0091] (Carboxyl amount)

[0092] Regarding the carboxyl group amount, 60 mL of a 0.5 mass % slurry (aqueous dispersion) of carboxylated cellulose was prepared, a 0.1 M aqueous hydrochloric acid solution was added to adjust the pH to 2.5, and then a 0.05 N aqueous sodium hydroxide solution was added dropwise. The conductivity was measured until the pH reached 11, and the amount of sodium hydroxide (a) consumed in the weak acid neutralization stage where the conductivity changes slowly was calculated using the following formula.

[0093] Carboxyl group amount [mmol / g carboxylated cellulose] = a [mL] × 0.05 / carboxylated cellulose mass [g].

[0094] (Degree of carboxymethyl substitution)

[0095] The degree of carboxymethyl substitution was determined by the following method.

[0096] Accurately weigh about 2.0g of the sample and put it in a 300mL stoppered conical flask. Add 100mL of the liquid obtained by adding 100mL of extra concentrated nitric acid to 1000mL of nitric acid methanol, and shake for 3 hours to convert the salt of carboxymethylated cellulose CNF (CMC) into H-CMC (hydrogen-type carboxymethylated CNF). Accurately weigh 1.5g to 2.0g of the absolutely dry H-CMC and put it in a 300mL stoppered conical flask. Moisten the H-CMC with 15mL of 80% methanol, add 100mL of 0.1N-NaOH, and shake at room temperature for 3 hours. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1N-H2SO4, and calculate the degree of carboxymethyl substitution (DS value) by the following formula.

[0097] A=[(100×F'-0.1N-H2SO4(mL)×F)×0.1] / (absolute dry mass of H-CMC(g))

[0098] Carboxymethyl substitution degree = 0.162×A / (1-0.058×A)

[0099] F': Factor of 0.1N-NaOH

[0100] F: Factor of 0.1N-H2SO4

[0101] The degree of carboxymethyl substitution of carboxymethylated cellulose CNF is generally the same as the degree of carboxymethyl substitution of carboxymethylated cellulose before being made into CNF.

[0102] (Crystallinity of Cellulose Type I)

[0103] The crystallinity of cellulose I type of carboxymethylated cellulose nanofibers was measured by the following method.

[0104] The sample was placed in a glass cell and measured using an X-ray diffraction measuring device (LabX XRD-6000, manufactured by Shimadzu Corporation). The crystallinity was calculated using the method of Segal et al., using the diffraction intensity of 2θ = 10° to 50° of the X-ray diffraction pattern as the baseline, and the diffraction intensity of the 002 plane at 2θ = 22.6° and the diffraction intensity of the amorphous part at 2θ = 18.5°, and calculated by the following formula.

[0105] Xc=(I002c-Ia) / I002c×100

[0106] Xc = Crystallinity of cellulose type I (%)

[0107] I002c: 2θ=22.6°, diffraction intensity of 002 surface

[0108] Ia: 2θ=18.5°, diffraction intensity of the amorphous part

[0109] The proportion of type I crystals of carboxymethylated cellulose nanofibers is generally the same as that of carboxymethylated cellulose before being made into CNFs.

[0110] (Amount of phosphorus oxyacid groups)

[0111] The amount of phosphorus oxyacid groups (the amount of phosphoric acid groups or phosphorous acid groups) is measured by the following method.

[0112] First, ion exchange water was added to the CNF to prepare a slurry having a solid content concentration of 0.2 mass %. The obtained slurry was treated with an ion exchange resin and then titrated with an alkali for measurement.

[0113] The treatment with ion exchange resin was performed as follows: 1 / 10 by volume of a strongly acidic ion exchange resin (Amber Jet 1024; Organo Co., Ltd., adjusted) was added to the above-mentioned CNF-containing slurry, and the mixture was shaken for 1 hour, and then injected onto a sieve with a mesh of 90 μm to separate the resin from the slurry.

[0114] In addition, the titration using alkali is performed as follows: 10 μL of 0.1N sodium hydroxide aqueous solution is added to the slurry containing CNF treated with ion exchange resin every 5 seconds, and the change in pH value displayed by the slurry is measured. It should be noted that nitrogen gas is blown into the slurry from 15 minutes before the start of the titration, and the titration is performed simultaneously. In this neutralization titration, in the curve obtained by plotting the measured pH relative to the amount of alkali added, two points where the increment (the differential value of pH to the amount of alkali added) reaches a maximum are observed. Among these points, the maximum point of the increment first obtained after adding the alkali is called the first end point, and the maximum point of the increment obtained next is called the second end point. The amount of alkali required from the start of the titration to the first end point is equal to the amount of the first dissociated acid in the slurry used in the titration. In addition, the amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used in the titration. The amount of alkali (mmol) required from the start of titration to the first endpoint was divided by the solid content (g) in the slurry to be titrated, and the value obtained was taken as the amount of phosphorus oxyacid groups (mmol / g).

[0115] (Determination of water content)

[0116] The moisture content in the powder was calculated using the difference between the mass of the obtained powder after drying at 105° C. for 3 hours or more (absolute dry mass) and the mass before drying.

[0117] (Average particle size)

[0118] The average particle size (D50) of the powders used in Examples and Comparative Examples was determined from particle size distribution based on volume average particle size.

[0119] The particle size distribution was measured using a laser diffraction scattering particle size distribution analyzer (MASTER SIZER 3000, manufactured by Spectris Corporation) under the condition that the particle refractive index was 1.5. During the measurement, a dry powder sample was directly placed in the device for measurement.

[0120] (Dispersion)

[0121] The dispersibility of the powders obtained in the examples and comparative examples was measured using a powder tester (Powder Tester PT-X, manufactured by Hosokawa Micron Co., Ltd.) Specifically, when 10 g of a sample was placed in the dispersing unit of the PT-X and allowed to fall, the dispersibility was calculated from the amount of powder that fell on the watch glass using the following formula.

[0122] Dispersion (%) = (10 (g) - the amount of powder falling on the watch glass (g)) / 10 (g)

[0123] (angle of repose)

[0124] The angle of repose of the powder obtained in the examples and comparative examples is the value of the Angle Repose when the powder is dropped from the hole of a funnel using a powder tester (PowderTester PT-X, manufactured by Hosokawa Micron Co., Ltd.) and deposited on a horizontal plate of a certain area until it becomes a certain shape to form a conical granule.

[0125] (Crash Angle)

[0126] For the collapse angle of the powder obtained in the examples and comparative examples, a powder property tester (PowderTester PT-X, manufactured by Hosokawa Micron Co., Ltd.) was used to make the powder fall from the hole of a funnel and accumulate on a horizontal plate of a certain area until it becomes a certain shape, forming a conical granule. Then, a certain impact was applied to the powder by dropping a weight of a certain weight located on the same base as the horizontal plate, and a part of the powder naturally flowed and fell off the horizontal plate. The elevation angle of the remaining conical granule from the point on the outer periphery of the bottom surface to the apex of the cone was taken as the collapse angle.

[0127] (Difference angle)

[0128] The difference angle is calculated by the following formula using the repose angle and collapse angle measured above.

[0129] Differential angle = repose angle - collapse angle

[0130] (Workability during packaging)

[0131] The workability during packaging of the powders obtained in Examples and Comparative Examples was checked: a polyethylene bag was filled with sample powder to 70% of the bag and sealed, the sealed portion was visually checked, and the evaluation was performed according to the following criteria.

[0132] A: There is little powder scattering, no powder adheres to the sealing adhesive part, and the sealing performance is almost not reduced

[0133] B: Powder is scattered and adheres to the sealing part, and the sealing performance is slightly reduced

[0134] C: There is a lot of powder scattering, a large amount of powder adheres to the sealing adhesive part, and the sealing performance is greatly reduced

[0135] (Evaluation of initial water absorption)

[0136] The water absorption in a short period of time (initial water absorption) was evaluated for the powders obtained in the examples and comparative examples. 0.1 g of the sample was placed flat on a rectangular glass plate. Then, the water absorption immediately after 1 mL of pure water was uniformly dropped onto the sample using a dropper was evaluated according to the following criteria.

[0137] A: Immediately after the drop is added, water is absorbed into the powder and a gel layer is formed on the whole.

[0138] B: Immediately after the drop is added, the water absorption into the powder is slow, and a part of it forms a gel layer, but the remaining pure water separates into droplets on the powder

[0139] C: Immediately after the drop is added, the water absorption into the powder is slow, and most of the pure water separates into droplets on the powder

[0140] (Production Example 1)

[0141] (Production of Carboxylated CNF1)

[0142] 500 g (absolutely dry) of bleached unbeaten kraft pulp (whiteness 85%) from conifers was added to 20 L of an aqueous solution in which TEMPO (Sigma Aldrich) (0.025 mmol / g relative to the cellulose raw material) and sodium bromide (1 mmol / g relative to the cellulose raw material) were dissolved, and the mixture was stirred until the pulp was evenly dispersed. An aqueous sodium hypochlorite solution was added to the reaction system to make it 5.2 mmol / g, and the oxidation reaction was started. During the reaction, the pH in the system decreased, and 3M sodium hydroxide aqueous solution was added successively to adjust the pH to 10. Sodium hypochlorite was consumed, and the reaction was terminated at the moment when the pH in the system no longer changed. The mixture after the reaction was filtered through a glass filter, the pulp was separated, and the pulp was fully washed with water to obtain an oxidized pulp (carboxylated cellulose). The pulp yield at this time was 90%, the time required for the oxidation reaction was 100 minutes, and the carboxyl amount was 1.4 mmol / g.

[0143] The oxidized pulp obtained in the above step was adjusted to 1.0% (weight / volume) with water and treated three times with an ultra-high pressure homogenizer (20°C, 150 MPa) to obtain a dispersion of carboxylated CNF 1. The average fiber diameter of the obtained fiber was 4 nm and the aspect ratio was 220.

[0144] (Production Example 2)

[0145] (Production of Carboxylated CNF2)

[0146] 500 g (absolutely dry) of bleached dissolving kraft pulp from coniferous trees (manufactured by Buckeye, DKP) was added to 50 L of an aqueous solution in which 7.8 g (0.05 mole) of TEMPO (Sigma Aldrich) and 75.5 g (0.74 mole) of sodium bromide were dissolved, and the mixture was stirred until the pulp was uniformly dispersed. 1.6 L of a 2M aqueous sodium hypochlorite solution was added to the reaction system, and then an oxidation reaction (oxidation treatment) was started. During the reaction, the pH in the system decreased, and a 3M aqueous sodium hydroxide solution was added successively to adjust the pH to 10. After reacting for 2 hours, the mixture was filtered with a glass filter and washed thoroughly with water, thereby obtaining carboxylated cellulose. A slurry of carboxylated cellulose adjusted to 5.0% (weight / volume) with water was prepared, to which hydrogen peroxide was added at 2% (weight / weight) relative to the carboxylated cellulose, and the pH was adjusted to 11.3 with 3M sodium hydroxide. The slurry was placed at a temperature of 80°C for 2 hours for hydrolysis. The concentration was adjusted to 5.0% (weight / volume) with water and treated 5 times with an ultra-high pressure homogenizer (20°C, 140 MPa) to obtain a dispersion of carboxylated CNF2. The carboxyl group content of the obtained carboxylated CNF2 was 1.7 mmol / g, the average fiber diameter was 3 nm, and the aspect ratio was 117.

[0147] (Production Example 3)

[0148] (Production of Carboxymethylated CNF)

[0149] In a 5L capacity biaxial kneader with a rotation speed adjusted to 100 rpm, 500 parts of isopropyl alcohol (IPA) and 15 parts of sodium hydroxide dissolved in 200 parts of water were added, and 100 parts of hardwood pulp (LBKP manufactured by Nippon Paper Industries, Ltd.) were added in terms of dry mass when dried at 100°C for 60 minutes. Mercerized cellulose was prepared by stirring and mixing at 30°C for 90 minutes. Further, while stirring, 19 parts of sodium monochloroacetate dissolved in 20 parts of 90% IPA were added, stirred at 30°C for 30 minutes, and then heated to 70°C, and a carboxymethylation reaction was carried out at 70°C for 90 minutes. After the reaction was completed, neutralization was carried out, washing was carried out with 65% aqueous methanol, deliquoring, drying, and pulverization were carried out, thereby obtaining a sodium salt of carboxymethylated cellulose with a carboxymethyl substitution degree of 0.18 and a cellulose I type crystallinity of 64%. The methods for measuring the degree of carboxymethyl substitution and the crystallinity of cellulose I are as described above.

[0150] The sodium salt of carboxymethylated cellulose obtained in the above step was adjusted to 1.0% (weight / volume) with water, and treated three times with an ultra-high pressure homogenizer (20°C, 150 MPa) to obtain a dispersion of carboxymethylated CNF. The average fiber diameter of the obtained carboxymethylated CNF was 8 nm and the aspect ratio was 60.

[0151] (Production Example 4)

[0152] (Production of Phosphorylated CNF)

[0153] Bleached unbeaten kraft pulp (brightness 85%, basis weight 245 g / m2) from coniferous trees was prepared as follows: 2Flakes) are subjected to phosphorus oxygen acidification treatment. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea is added to 100 parts by mass (absolutely dry) of the above-mentioned raw material pulp, and the ammonium dihydrogen phosphate is adjusted to 45 parts by mass, the urea is adjusted to 120 parts by mass, and the water is adjusted to 150 parts by mass, thereby obtaining a chemical solution impregnated pulp. Next, the obtained chemical solution impregnated pulp is heated for 250 seconds using a hot air dryer at 165°C to introduce phosphoric acid groups into the cellulose in the pulp, thereby obtaining a phosphorylated pulp. 10L of ion exchange water is injected into 100g (absolutely dry) of the obtained phosphorylated pulp to obtain a pulp dispersion, the obtained pulp dispersion is stirred to make the pulp evenly dispersed, and then the filtering and dehydrating operations are repeated for washing. The moment when the conductivity of the filtrate reaches 100μS / cm or less is regarded as the end point of washing. Next, the washed phosphorylated pulp was diluted with 10 L of ion exchange water, and then a 1N sodium hydroxide aqueous solution was added little by little while stirring, thereby obtaining a phosphorylated pulp slurry having a pH of 12 to 13. The phosphorylated pulp slurry was dehydrated and washed to obtain a neutralized phosphorylated pulp.

[0154] The infrared absorption spectrum of the phosphorylated pulp obtained was measured using FT-IR. -1 Absorption of P=O based on phosphate groups was observed near the phosphate group, confirming that phosphate groups were added to the pulp. In addition, the obtained phosphated pulp was subjected to testing and analyzed using an X-ray diffraction device. As a result, typical peaks were confirmed at two positions near 2θ=14° to 17° and near 2θ=22° to 23°, confirming the presence of cellulose I type crystals.

[0155] The phosphorylated pulp obtained in the above step was adjusted to 1.0% (weight / volume) with water and treated three times with an ultra-high pressure homogenizer (20°C, 150 MPa) to obtain a dispersion of phosphorylated CNF. The obtained fibers had an average fiber diameter of 4 nm and an aspect ratio of 200.

[0156] X-ray diffraction confirmed that the obtained CNF maintained cellulose I-type crystals. In addition, the amount of phosphate groups (first dissociated acid amount) was 1.45 mmol / g. In addition, the total dissociated acid amount was 2.45 mmol / g.

[0157] (Example 1)

[0158] (Manufacturing of dried body)

[0159] As anion-modified CNF, carboxylated CNF1 (carboxyl group amount: 1.4 mmol / g, average fiber diameter: 4 nm, aspect ratio: 220) obtained in Preparation Example 1 was used. 40% by mass of carboxymethyl cellulose (trade name: F350HC-4, viscosity (1%, 25°C) about 3000 mPa·s, carboxymethyl substitution degree of about 0.9) was added to a 0.7% by mass aqueous suspension of carboxylated CNF1 relative to the anion-modified CNF (i.e., when the solid content of the anion-modified CNF is set to 100 parts by mass, the solid content of the carboxymethyl cellulose is 40 parts by mass), and stirred for 60 minutes using a TK homomixer (12000 rpm), thereby preparing an aqueous dispersion containing anion-modified CNF. The pH of the dispersion is about 7 to about 8. 5% sodium hydroxide aqueous solution was added to the aqueous dispersion to adjust the pH to 9, and then coated on the surface of the drum of a drum dryer D0405 (manufactured by Katsuragi Industries) to form a thin film with a thickness of about 100 μm to about 200 μm. The film was dried under the conditions of a drum surface temperature of 80°C, a pressure in the dryer of 2 kPa, and a drum rotation speed of 2 rpm to obtain a dried body of anion-modified CNF containing 5% by mass of water.

[0160] (Manufacturing of powder)

[0161] The dried body containing CNF obtained as described above was crushed by using a hammer mill (manufactured by Tokyo Atomizer, Hammer Mill TAP-3) as a pulverizer to prepare a pulverized product. For the obtained pulverized product, the particle size was adjusted by adjusting the sieve diameter of the pulverizer outlet. The pulverized product after adjusting the particle size was recovered using a cyclone separator to obtain a powder containing anion-modified CNF. The moisture content of the obtained powder was 8% by mass.

[0162] (Example 2)

[0163] Except that the dried body containing CNF obtained in Example 1 was crushed by an impact mill (manufactured by Hosokawa Micron Co., Ltd., Pulverizer) instead of a hammer mill as a pulverizer, a pulverized product was obtained in the same manner as in Example 1. For the obtained pulverized product, the particle size was adjusted by adjusting the rotation speed of the classification rotor. The pulverized product after adjusting the particle size was recovered using a cyclone separator, thereby obtaining a powder containing anion-modified CNF. The moisture content of the obtained powder was 10% by mass.

[0164] (Example 3)

[0165] The dried body containing CNF obtained in Example 1 was pulverized by a disc mill (Centricutter, manufactured by Coke Industries, Japan) instead of a hammer mill as a pulverizer, and a pulverized product was obtained in the same manner as in Example 1. The pulverized product was recovered using a cyclone separator to obtain a powder containing anion-modified CNF. The moisture content of the obtained powder was 9.7% by mass.

[0166] (Example 4)

[0167] The dried body containing CNF obtained in Example 1 was crushed by an impact mill (manufactured by Tokyo Atomizer Manufacturing Co., Ltd., Atomizer) instead of a hammer mill as a pulverizer, and a crushed product was obtained in the same manner as in Example 1. The obtained crushed product was adjusted and recovered in the same manner as in Example 1 to obtain a powder containing anion-modified CNF. The moisture content of the obtained powder was 9.3% by mass.

[0168] (Example 5)

[0169] Except using Turbo Mill (manufactured by Freund Industry Co., Ltd.) as a pulverizer to pulverize the dried body containing CNF obtained in Example 1, the pulverized material was obtained in the same manner as in Example 1. For the obtained pulverized material, the particle size was adjusted by adjusting the gap between the rotor and the bushing. The pulverized material after adjusting the particle size was recovered using a cyclone separator, thereby obtaining a powder containing anion-modified CNF. The moisture content of the obtained powder was 7.8% by mass.

[0170] (Example 6)

[0171] (Manufacturing of dried body)

[0172] As anion-modified CNF, carboxymethylated CNF (carboxymethyl substitution degree: 0.18, average fiber diameter: 8 nm, aspect ratio: 60) obtained in Preparation Example 3 was used. 40% by mass of carboxymethyl cellulose (manufactured by Nippon Paper Industries, Ltd., trade name: F350HC-4, viscosity (1% by mass, 25° C., 60 rpm) about 3000 mPa·s, carboxymethyl substitution degree of about 0.90) was added to a 0.7% by mass aqueous suspension of carboxymethylated CNF (i.e., when the solid content of the carboxymethylated CNF was 100 parts by mass, the solid content of the carboxymethyl cellulose was 40 parts by mass), and stirred for 60 minutes using a TK homomixer (12000 rpm), thereby preparing an aqueous dispersion containing carboxymethylated CNF as anion-modified CNF. 5 mass % of sodium hydroxide aqueous solution was added to the aqueous dispersion to adjust the pH to 9, and then applied to the drum surface of drum dryer D0405 (manufactured by Katsuragi Industries) and dried at 140° C. for 1 minute. The obtained dried product was scraped to obtain a dried product containing anion-modified CNF.

[0173] (Manufacturing of powder)

[0174] The dried body containing CNF obtained as described above was crushed in the same manner as in Example 2 to obtain a crushed product. The particle size of the crushed product was adjusted by adjusting the rotation speed of the classification rotor. The crushed product after adjusting the particle size was recovered using a cyclone separator to obtain a powder containing anion-modified CNF. The moisture content of the obtained powder was 8.2% by mass.

[0175] (Example 7)

[0176] A dried body containing anion-modified CNF was prepared in the same manner as in Example 2, except that the phosphorylated CNF (phosphate group amount: 1.45 mmol / g, average fiber diameter: 4 nm, aspect ratio: 200) obtained in Preparation Example 4 was used as the anion-modified CNF. The dried body was crushed in the same manner as in Example 2 to obtain a crushed product. The particle size of the obtained crushed product was adjusted by adjusting the rotation speed of the classification rotor. The crushed product after the particle size was adjusted was recovered using a cyclone separator to obtain a powder containing phosphorylated CNF. The moisture content of the obtained powder was 8.5% by mass.

[0177] (Comparative Example 1)

[0178] (Manufacturing of dried body)

[0179] As anion-modified CNF, a 5.0 mass % aqueous suspension (pH 7.5) of the carboxylated CNF2 (carboxyl group content: 1.7 mmol / g, average fiber diameter: 3 nm, aspect ratio: 117) obtained in Preparation Example 2 was prepared and dried using a two-fluid nozzle spray drying device (manufactured by Okawara Chemical Industry Co., Ltd., OUDT-25) under the conditions of an inlet temperature of 160°C, an outlet temperature of 70°C, a drying air volume of 80 kg / hour, and a liquid delivery volume of 54.2 kg / hour to obtain a powdered CNF dry body.

[0180] The obtained dried product was collected using a cyclone separator to obtain anion-modified CNF powder. The moisture content of the obtained powder was 4.4% by mass.

[0181]

[0182] As can be seen from Table 1, the powder of anionically modified cellulose nanofibers with a fiber diameter of 3nm to 500nm in Examples 1 to 7, which have a moisture content of less than 20% by mass, an average particle size of more than 45μm, and a dispersion of less than 25%, has a suppressed amount of scattering in the process and excellent handling. Moreover, the workability during packaging is excellent. In addition, the initial water absorption is good. This shows that, for example, when the powder is added to a tank filled with water and redispersed, the powder is not easy to float on the water surface, and the powder is easy to suspend in the water, and it can be considered that the dispersion and homogenization in water by stirring are excellent. On the other hand, the dispersion of the anionically modified cellulose nanofiber powder of Comparative Example 1 with a small average particle size is outside the above range, and it is difficult to suppress the amount of scattering in the process, and the handling is poor. Moreover, the workability during packaging is poor, and poor sealing during packaging may occur. Moreover, the initial water absorption is slow, and the water and powder are separated and difficult to merge.

[0183] In general, various adjustments are made to the cellulose nanofiber powder to ensure the redispersibility of the cellulose nanofiber powder when the cellulose nanofiber powder is redispersed in a solvent. Therefore, even the cellulose nanofiber powders have weaker adhesion between the powders than the ordinary cellulose powders, and thus are likely to be easily scattered and the workability is likely to be deteriorated compared to the ordinary cellulose powders.

[0184] It has been clarified for the first time that the anionically modified cellulose nanofiber powder of the present invention can obtain a cellulose nanofiber powder having excellent workability and suppressed scattering by adjusting the moisture content, average particle size and dispersion degree to an appropriate balance even for cellulose nanofibers having good redispersibility.

Claims

1. A powder containing anionic modified cellulose nanofibers, containing anionic modified cellulose nanofibers with an average fiber diameter of 3nm to 500nm, wherein: The powder containing anionic modified cellulose nanofibers has a moisture content of 20 mass % or less, an average particle size of 45 μm or more, and a dispersion degree of less than 25%.

2. The powder containing anionic modified cellulose nanofibers according to claim 1, wherein: The angle of repose of the powder containing anionic modified cellulose nanofibers is 40° to 49°.

3. The powder containing anionic modified cellulose nanofibers according to claim 1, wherein The collapse angle of the powder containing anionic modified cellulose nanofibers is 15° to 24°.

4. The powder containing anionic modified cellulose nanofibers according to claim 1, wherein The difference angle of the powder containing anion-modified cellulose nanofibers is 20° to 25°.

Citation Information

Patent Citations

  • Method for producing cellulose nanofiber dry solid

    WO2019189318A1